Low-moisture composite diaphragm as well as preparation method and application thereof

By coating the coated electrolyte material of fluorine-containing compounds combined with inorganic solid electrolyte powder on the surface of the lithium-ion battery separator, the thermal stability and moisture adsorption of the separator under high temperature conditions are solved, and low moisture and high ionic conductivity are achieved , extends the battery cycle life and improves safety performance.

CN119315215AInactive Publication Date: 2025-01-14JINLONGYU NEW ENERGY (SHENZHEN) CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411599284.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have poor thermal stability under high temperature conditions, are prone to thermal shrinkage, and have poor affinity with the electrolyte, resulting in reduced battery circulation and safety performance.

Method used

A low-moisture composite separator is used to coat the surface of the separator with a coated electrolyte material formed by combining fluorine-containing compounds with inorganic solid electrolyte powder, which reduces moisture adsorption, enhances ionic conductivity, and improves hydrophobicity and puncture strength.

Benefits of technology

Significantly reduce the moisture content in the diaphragm, improve the ionic conductivity and puncture strength of the diaphragm, extend the battery cycle life, and improve safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127827540000071
    Figure BDA0005127827540000071
Patent Text Reader

Abstract

The invention relates to a low-moisture composite diaphragm as well as a preparation method and application thereof, and belongs to the technical field of methods or devices for directly converting chemical energy into electric energy. The low-moisture composite diaphragm comprises a diaphragm substrate and a coating arranged on at least one side surface of the diaphragm substrate, the coating comprises a coating electrolyte material, a thickening agent and an adhesive; the coated electrolyte material comprises inorganic solid electrolyte powder and a coating layer on the surface of the inorganic solid electrolyte powder; the coating layer is mainly formed by a fluorine-containing compound, and the fluorine-containing compound comprises at least one of a fluorine-containing and unsaturated double bond compound, a fluorinated coupling agent and a fluorine-containing high-molecular compound. The low-moisture composite diaphragm has both low moisture content and high ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of methods or devices for directly converting chemical energy into electrical energy, and in particular to a low-moisture composite diaphragm and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are usually composed of positive electrode materials, negative electrode materials, separators and electrolytes. The separator with a microporous structure is located between the positive electrode materials and the negative electrode materials of the lithium-ion battery to ensure the free passage of lithium ions and prevent the passage of electrons. The structure and performance of the separator have an important influence on the battery's capacity, resistance and life, and will also determine the battery's safety performance to a certain extent. Polyolefin separators (polyethylene separators or polypropylene separators, etc.) are the lithium-ion battery separators with the highest market share. They not only have good mechanical properties, but also have excellent electrochemical stability; however, their thermal stability is poor, they are prone to thermal shrinkage under high temperature conditions, and their affinity with the electrolyte is poor.

[0003] At present, polyolefin separators are mostly modified by grafting modification, coating modification, development of new materials or new processing technology. Among them, coating modification is mainly a method of coating inorganic ceramic particles on a polyolefin separator or a new material separator as a supporting base membrane. This method introduces a coating on the surface of the polyolefin separator to enhance the liquid absorption and retention, high temperature resistance or flame retardancy of the separator, thereby extending the battery cycle life and improving the safety of the battery. For example, aluminum oxide is coated on the surface of the polyolefin separator to play a role in thermal support and improve the liquid retention capacity, so as to improve the battery's cycle performance and safety performance. However, in actual application, it is found that the hardness and density of aluminum oxide are relatively large, which can easily lead to severe wear of equipment in the production process and also lead to low energy density of the battery.

[0004] Compared with alumina, inorganic solid electrolyte materials not only have lower hardness and density, but can also use the lithium they contain to compensate for the lithium loss of lithium-ion batteries during the cycle process. However, they are easy to precipitate ions in water, resulting in a coating on the surface of the polyolefin separator containing more water. This water content will further cause the decomposition of lithium salts in the electrolyte, thereby destroying SEI and corroding the current collector, thereby significantly reducing the battery's cycle performance and safety performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a low-moisture composite diaphragm and a preparation method and application thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a low-moisture composite diaphragm, which includes a diaphragm substrate and a coating disposed on at least one side of the diaphragm substrate; the coating includes a coated electrolyte material, a thickener and an adhesive;

[0008] The coated electrolyte material includes an inorganic solid electrolyte powder and a coating layer on the surface of the inorganic solid electrolyte powder; the coating layer is mainly formed by a fluorine-containing compound, and the fluorine-containing compound includes at least one of a fluorine-containing and unsaturated double bond compound, a fluorinated coupling agent, and a fluorine-containing polymer compound.

[0009] The present invention combines fluorine-containing compounds with inorganic solid electrolyte powders to form a coated electrolyte material with good hydrophobicity and excellent ionic conductivity. After the coating containing the coated electrolyte material is set on the surface of the diaphragm, it can not only effectively reduce the contact between moisture and the diaphragm, but also further reduce the adsorption of moisture by the diaphragm, thereby significantly reducing the water content in the diaphragm; it can also use the inorganic solid electrolyte to enhance the ionic conductivity of the diaphragm, thereby giving the diaphragm low moisture and high ionic conductivity.

[0010] In addition, the mass fraction of the coated electrolyte material in the coating of the above-mentioned low-moisture composite diaphragm is greater than or equal to 70%, and the coating with a high content of coated electrolyte material can give the diaphragm good puncture strength and liquid retention performance. Optionally, the above-mentioned diaphragm can be a polyolefin diaphragm (PE microporous membrane, PP microporous membrane, PE and PP composite multilayer microporous membrane, etc.) or a non-woven fabric diaphragm (polyimide membrane, polyester membrane, cellulose membrane, polyamide membrane, aramid membrane, spandex membrane, etc.).

[0011] Optionally, the above-mentioned fluorine-containing and unsaturated double bond compounds include at least one of perfluoroalkyl acrylate compounds, fluoroalkyl silanes, and perfluoropolyethers; the fluorinated coupling agent includes at least one of trifluoropropyl methylcyclotrisiloxane, heptadecafluorodecyltrimethylsilane, trifluoropropyltrimethoxysilane, and triethoxysilane; the fluorine-containing polymer compound includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, perfluoroalkyl vinyl ether copolymer, polyperfluoroethylene propylene, tetrafluoroethylene-hexafluoropropylene-trifluoroethylene copolymer, and polyvinylidene fluoride-hexafluoropropylene.

[0012] Optionally, the inorganic solid electrolyte powder can be purchased or synthesized by conventional methods, and can be specifically a garnet-type solid electrolyte, a perovskite-type solid electrolyte, and a NASICON-type solid electrolyte; wherein the chemical formula of the garnet-type solid electrolyte is Li 7-x Ln3Z 2-x M x O 12 , M is at least one of Ta, Nb, Hf, Al, Si, Ga, Ge, Sc, Ti, V, Y, and Sn; the perovskite-type solid electrolyte may be Li3 / 8 Sr 7 / 16 Ta 3 / 4 Zr 1 / 4 O3 or Li 3 / 8 Sr 7 / 16 Ta 3 / 4H 1 / 4 O3; the chemical formula of NASICON solid electrolyte is LiM(PO4)3, where M is selected from Na + , Nb 5+ 、 5+ 、Ti 4+ ,Ge 4+ 、Zr 4 + Sn 4+ , Nb 4+ , Hf 4+ 、Al 3+ Cr 3+ , Ga 3+ , Fe 3+ Sc 3+ 、In + , Y 3+ ,La 3+ Mg 2+ 、Zn 2+ , Cu 2+ 、Co 2+ , Mn 2+ , Fe 2+ At least one of .

[0013] As a preferred embodiment of the low-moisture composite diaphragm of the present invention, the mass ratio of the inorganic solid electrolyte powder to the fluorine-containing compound is 10:(0.05-1). Optionally, the mass ratio of the inorganic solid electrolyte powder to the fluorine-containing compound can be specifically 10:0.1, 10:0.2, 10:0.3, 10:0.4, 10:0.5, 10:0.6, 10:0.7, 10:0.8, 10:0.9. Studies have found that when the mass ratio of the inorganic solid electrolyte powder to the fluorine-containing compound is within the above range, the coated electrolyte material can have high ionic conductivity while having better hydrophobic properties.

[0014] As a preferred embodiment of the low-moisture composite separator of the present invention, the particle size D50 of the coated electrolyte material is 0.1-2 μm. Optionally, the particle size D50 of the coated electrolyte material can be 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm.

[0015] As a preferred embodiment of the low-moisture composite separator of the present invention, the mass ratio of the coated electrolyte material, thickener and adhesive is (60-98):(0.5-10):(0.5-10). Optionally, by weight, the coated electrolyte material can be 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, the thickener can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, and the adhesive can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts.

[0016] As a preferred embodiment of the low-moisture composite separator of the present invention, the average thickness of the coating is 0.5-4 μm. Optionally, the average thickness of the coating can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or 3.5 μm.

[0017] As a preferred embodiment of the low-moisture composite diaphragm described in the present invention, the compound containing fluorine and unsaturated double bonds is a perfluoroalkyl acrylate compound, and the perfluoroalkyl acrylate compound includes at least one of perfluoroalkyl ethyl acrylate, perfluoroalkyl propyl acrylate, perfluoroalkyl propyl methacrylate, perfluorooctyl ethyl acrylate, perfluorohexyl ethyl acrylate, 1H,1H,11H-perfluoroundecyl acrylate, and perfluorobutyl ethyl acrylate.

[0018] As a preferred embodiment of the low-moisture composite diaphragm of the present invention, the thickener includes at least one of carboxymethyl cellulose amine, carboxymethyl cellulose lithium, polyvinyl alcohol-polyacrylic acid copolymer, and hydrophobically modified alkali swelling thickener (STZC-95, STZC-915, etc.).

[0019] As a preferred embodiment of the low-moisture composite diaphragm of the present invention, the adhesive includes at least one of polyvinylidene fluoride, styrene-butadiene latex, polyacrylate, polymethyl methacrylate, and polyacrylic acid.

[0020] As a preferred embodiment of the low-moisture composite diaphragm of the present invention, the components of the coating further include a hydrophobic agent, and the hydrophobic agent includes at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

[0021] In a second aspect, the present invention provides a method for preparing the above-mentioned low-moisture composite diaphragm, comprising the following steps: firstly, uniformly mixing the coating electrolyte material and water with a dispersant, a thickener, an adhesive, a wetting agent and a hydrophobic agent to obtain a coating slurry; then, uniformly coating the coating slurry on the surface of the diaphragm substrate, and drying to obtain a low-moisture composite diaphragm;

[0022] The dispersant is at least one of ethanol, methanol, isopropanol, polyvinyl alcohol, acetone, methyl ether, silicate colloid, and propylene glycol block polyether; the wetting agent is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium butyl naphthalene sulfonate, and polyethylene glycol butyl ether.

[0023] In a third aspect, the present invention provides the use of the low-moisture composite diaphragm in batteries or capacitors.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention combines fluorine-containing compounds with inorganic solid electrolyte powders to form a coated electrolyte material with good hydrophobicity and excellent ionic conductivity. After the coating containing the coated electrolyte material is set on the surface of the diaphragm, it can not only effectively reduce the contact between moisture and the diaphragm, but also further reduce the adsorption of moisture by the diaphragm, thereby significantly reducing the water content in the diaphragm; it can also use the inorganic solid electrolyte to enhance the ionic conductivity of the diaphragm, thereby giving the diaphragm low moisture and high ionic conductivity. DETAILED DESCRIPTION

[0026] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0027] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.

[0028] Example 1

[0029] An embodiment of the low-moisture composite diaphragm of the present invention, a method for preparing the low-moisture composite diaphragm of this embodiment, comprises the following steps:

[0030] S1. Mix the inorganic solid electrolyte (LATP) powder and perfluoroalkyl ethyl acrylate in a mass ratio of 10:0.1 and then vacuum dry to obtain a coated electrolyte material (particle size D50 = 0.5 μm);

[0031] S2, first mix the coating electrolyte material in S1 with water, then continue to add dispersant (ethanol), thickener (carboxymethyl cellulose amine), adhesive (polyacrylate) and wetting agent (sodium dodecyl sulfate) and mix them evenly, then add hydrophobic agent (3-aminopropyltrimethylsilane) and mix them evenly to obtain coating slurry; wherein the mass fraction of water in the coating slurry is 60%, and the mass ratio of coating electrolyte material, dispersant, thickener, adhesive, wetting agent and hydrophobic agent is 82:2:3:8:3:2;

[0032] S3. Use extrusion coating to evenly apply the coating slurry in S2 on one side of a polyethylene diaphragm (thickness of 12 μm, porosity of 43%), and dry to obtain a low-moisture composite diaphragm (average thickness of the coating is 3 μm).

[0033] Example 2

[0034] An embodiment of the low-moisture composite membrane of the present invention, the preparation method of the low-moisture composite membrane in this embodiment is basically the same as that in Example 1, except that in step S1, the mass ratio of the inorganic solid electrolyte powder to the perfluoroalkyl ethyl acrylate is 10:0.5.

[0035] Example 3

[0036] An embodiment of the low-moisture composite membrane of the present invention, the preparation method of the low-moisture composite membrane in this embodiment is basically the same as that in Example 1, except that in step S1, the mass ratio of the inorganic solid electrolyte powder to the perfluoroalkyl ethyl acrylate is 10:1.

[0037] Example 4

[0038] An embodiment of the low-moisture composite membrane of the present invention, the preparation method of the low-moisture composite membrane in this embodiment is basically the same as that in Example 1, except that the perfluoroalkyl ethyl acrylate in step S1 is replaced by perfluoroalkyl propyl methacrylate.

[0039] Example 5

[0040] An embodiment of the low-moisture composite membrane of the present invention. The preparation method of the low-moisture composite membrane in this embodiment is basically the same as that in Example 1, except that in step S2, the mass ratio of the coated electrolyte material, dispersant, thickener, adhesive, wetting agent and hydrophobic agent is 84:2:3:8:3:0.

[0041] Example 6

[0042] An embodiment of the low-moisture composite diaphragm of the present invention. The preparation method of the low-moisture composite diaphragm described in this embodiment is basically the same as that in Example 1, except that the dispersant in step S2 is isopropyl alcohol and the thickener is sodium carboxymethyl cellulose; the mass ratio of the coating electrolyte material, dispersant, thickener, adhesive, wetting agent and hydrophobic agent is 77:3:2:10:5:3; the mass fraction of water in the coating slurry is 55%.

[0043] Example 7

[0044] An embodiment of the low-moisture composite diaphragm of the present invention. The preparation method of the low-moisture composite diaphragm in this embodiment is basically the same as that in Example 1, except that the inorganic solid electrolyte in step S1 is LAGP; the dispersant in step S2 is isopropanol; and the mass ratio of the coating electrolyte material, dispersant, thickener, adhesive, wetting agent and hydrophobic agent is 82:2:3:8:3:2.

[0045] Example 8

[0046] An embodiment of the low-moisture composite membrane of the present invention, the preparation method of the low-moisture composite membrane in this embodiment is basically the same as that in Example 1, except that the perfluoroalkylethyl acrylate in step S1 is replaced by perfluorodecyltriethoxysilane.

[0047] Example 9

[0048] An embodiment of the low-moisture composite membrane of the present invention. The preparation method of the low-moisture composite membrane in this embodiment is basically the same as that in Example 1, except that the perfluoroalkylethyl acrylate in step S1 is replaced by a polyvinylidene fluoride-hexafluoropropylene solution (the solvent is N-methylpyrrolidone, wherein the mass ratio of the inorganic solid electrolyte powder to the polyvinylidene fluoride-hexafluoropropylene is 10:0.1).

[0049] Comparative Example 1

[0050] A comparative example of the low-moisture composite diaphragm of the present invention, the preparation method of the low-moisture composite diaphragm in this comparative example comprises the following steps:

[0051] S1. First, mix the inorganic solid electrolyte (LATP, particle size D50 = 0.5 μm) and water evenly, then continue to add dispersant (ethanol), thickener (carboxymethyl cellulose amine), adhesive (polyacrylate) and wetting agent (sodium dodecyl sulfate) and mix evenly, then add hydrophobic agent (3-aminopropyltrimethylsilane) and mix evenly to obtain coating slurry; wherein the mass fraction of water in the coating slurry is 60%, and the mass ratio of inorganic solid electrolyte, dispersant, thickener, adhesive, wetting agent and hydrophobic agent is 82:2:3:8:3:2;

[0052] S2. Use extrusion coating to evenly apply the coating slurry in S1 on one side of a polyethylene diaphragm (thickness of 12 μm, porosity of 43%), and dry it to obtain a low-moisture composite diaphragm (the average thickness of the coating is 3 μm).

[0053] Comparative Example 2

[0054] A comparative example of the low-moisture composite diaphragm of the present invention, the preparation method of the low-moisture composite diaphragm in this comparative example comprises the following steps:

[0055] S1. First, mix the inorganic solid electrolyte (LATP, particle size D50 = 0.5 μm) and water evenly, then continue to add perfluoroalkyl ethyl acrylate, dispersant (ethanol), thickener (carboxymethyl cellulose amine), adhesive (polyacrylate) and wetting agent (sodium dodecyl sulfate) and mix evenly, then add hydrophobic agent (3-aminopropyltrimethylsilane) and mix evenly to obtain a coating slurry; wherein the mass fraction of water in the coating slurry is 60%, and the mass ratio of the inorganic solid electrolyte, dispersant, thickener, adhesive, wetting agent and hydrophobic agent is 82:2:3:8:3:2;

[0056] S2. Use extrusion coating to evenly apply the coating slurry in S1 on one side of a polyethylene diaphragm (thickness of 12 μm, porosity of 43%), and dry it to obtain a low-moisture composite diaphragm (the average thickness of the coating is 3 μm).

[0057] Performance Testing

[0058] 1) Air permeability: The air permeability of the low-moisture composite membrane in each embodiment and comparative example was tested using an air permeability meter, with reference to standard GB / T 36363-2018.

[0059] 2) Moisture content: A Karl Fischer moisture tester was used to test the moisture content of the low-moisture composite membranes in the embodiments and comparative examples.

[0060] 3) Ionic conductivity: The low-moisture composite diaphragm in each embodiment and comparative example was used as a battery diaphragm, and the battery diaphragm was sandwiched between two circular steel sheets to assemble a button cell, and then the impedance value (battery diaphragm) was tested at 25° C. using an electrochemical workstation (VIONIC, Switzerland) and the ionic conductivity (σ) was calculated by the following formula;

[0061] σ=d / (R*S), where d is the thickness of the battery separator, in cm; R is the bulk resistance of the battery separator, in Ω; S is the contact area between the battery separator and the steel sheet, in cm 2 .

[0062] Table 1 Performance of low moisture composite diaphragms in various embodiments and comparative examples

[0063]

[0064] According to the data in Table 1, the air permeability of the low-moisture composite membranes in Examples 1 to 9 is maintained at 258 to 288 s / 100 mL, and the moisture value is less than or equal to 705 ppm, and the ionic conductivity is 2.49×10 -4S / cm or more, indicating that the low-moisture composite diaphragm of the present invention has low moisture value and high ionic conductivity while maintaining good air permeability. In addition, according to Comparative Examples 1 and 2, it can be seen that the direct mixing of perfluoroalkyl ethyl acrylate with inorganic solid electrolyte and other components (dispersant, thickener, adhesive and wetting agent) can also reduce the moisture of the composite diaphragm to a certain extent, but the degree of improvement is extremely limited.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A low-moisture composite diaphragm, characterized in that: It includes a diaphragm substrate and a coating disposed on at least one side of the diaphragm substrate; the coating includes a coating electrolyte material, a thickener and an adhesive; The coated electrolyte material includes an inorganic solid electrolyte powder and a coating layer on the surface of the inorganic solid electrolyte powder; the coating layer is mainly formed by a fluorine-containing compound, and the fluorine-containing compound includes at least one of a fluorine-containing and unsaturated double bond compound, a fluorinated coupling agent, and a fluorine-containing polymer compound.

2. The low-moisture composite diaphragm according to claim 1, characterized in that: The mass ratio of the inorganic solid electrolyte powder to the fluorine-containing compound is 10:(0.05-1).

3. The low-moisture composite diaphragm according to claim 1, characterized in that: The particle size D50 of the coated electrolyte material is 0.1-2 μm.

4. The low-moisture composite diaphragm according to claim 1, characterized in that: The mass ratio of the coated electrolyte material, thickener and adhesive is (60-98):(0.5-10):(0.5-10).

5. The low-moisture composite diaphragm according to claim 1, characterized in that: The average thickness of the coating is 0.5-4 μm.

6. The low-moisture composite diaphragm according to claim 1, characterized in that: The compound containing fluorine and unsaturated double bonds is a perfluoroalkyl acrylate compound; The perfluoroalkyl acrylate compound includes at least one of perfluoroalkyl ethyl acrylate, perfluoroalkyl propyl acrylate, perfluoroalkyl propyl methacrylate, perfluorooctyl ethyl acrylate, perfluorohexyl ethyl acrylate, 1H,1H,11H-perfluoroundecyl acrylate, and perfluorobutyl ethyl acrylate.

7. The low-moisture composite diaphragm according to claim 1, characterized in that: The thickener includes at least one of carboxymethyl cellulose amine, carboxymethyl cellulose lithium, polyvinyl alcohol-polyacrylic acid copolymer, and hydrophobically modified alkali swelling thickener; And / or, the adhesive includes at least one of polyvinylidene fluoride, styrene-butadiene latex, polyacrylate, polymethyl methacrylate, and polyacrylic acid.

8. The low-moisture composite diaphragm according to claim 1, characterized in that: The coating also includes a hydrophobic agent in its components, and the hydrophobic agent includes at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

9. The method for preparing the low-moisture composite diaphragm according to any one of claims 1 to 8, characterized in that: The following steps are involved: First, the coating electrolyte material and water are mixed evenly with a dispersant, a thickener, an adhesive, a wetting agent and a hydrophobic agent to obtain a coating slurry; then the coating slurry is evenly coated on the surface of the diaphragm substrate and dried to obtain a low-moisture composite diaphragm; The dispersant is at least one of ethanol, methanol, isopropanol, polyvinyl alcohol, acetone, methyl ether, silicate colloid, and propylene glycol block polyether; the wetting agent is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium butyl naphthalene sulfonate, and polyethylene glycol butyl ether.

10. Use of the low-moisture composite diaphragm according to any one of claims 1 to 8 in batteries or capacitors.

Citation Information

Patent Citations

  • Coated particles, positive electrode, negative electrode, all-solid-state battery, and coating composition for sulfide-based all-solid-state batteries

    CN112969730A

  • Composite diaphragm and preparation method thereof

    CN113540697A

  • Diaphragm containing mixed conductor coating and preparation method and application thereof

    CN114156600A

  • Coated composite material, pole piece and battery

    CN116314715A

  • Composite material, preparation method thereof and all-solid-state lithium battery

    CN117776258A